Fourth-generation corporate security asymmetrical warfare for protective services professionals - Godlewski, R.J (Create Space Independent Publishing Platform, 2014)
Discusses the challenges of fourth-generation warfare (4GW) in the context of private security operations throughout the world, including urban warfare, maritime, and executive protection scenarios. Fourth-Generation Corporate Security (4GCS) cannot be taught - it must be learned through experience and intuition. Accordingly, this offering by R.J. Godlewski provides the foundation upon which the security professional can build his or her repertoire and arsenal in combating the apparitional nature of asymmetrical conflicts.